PERENCANAAN PRODUKSI JAMUR TIRAM DI PT GAYA GREEN SRIKANDI DENGAN PENDEKATAN LINEAR PROGRAMMING - Wira Nanda, Hotlas
Oyster mushrooms are widely consumed by the community as one of the preferred food choices due to their high nutritional content, which is beneficial for human health. The increasing awareness regarding the nutritional benefits of oyster mushrooms has led to a higher demand for them. However, PT Gaya Green Srikandi, one of the oyster mushroom cultivation businesses, has been unable to meet the demand so the company is committed to seeking ways to increase production. Additionally, the company has not yet maximized its production capacity and lacks a formal production planning model for oyster mushrooms. Therefore, the focus of this research is to develop a production planning model by considering the production capacity of each process involved in oyster mushroom production. The production capacity planning model in this research is developed using the linear programming method to determine the total daily production of baglog in one year. The search for a solution to this production capacity planning model is conducted with the assistance of the IBM ILOG CPLEX Optimization Studio 12.10.0 software. This model generates decisions regarding the daily production of baglog. Once the daily production of baglog is determined, the results are allocated to each cultivation house and arranged production schedules by considering the company's standard rules. Based on the solution obtained from the linear programming model, the total daily production of baglog for a one-year planning period is 1,222,036 baglogs, with daily production divided into 4,500 baglogs, 2,276 baglogs, and 0 baglog. This means that there are days when the company does not need to carry out production activities. By comparing the results with historical data from October 2022 to May 2023, this research model shows an increase in the production of baglog and the potential for an increase in oyster mushroom harvest by 57.45%. By implementing this model, the company can increase the percentage of fulfilling the demand for oyster mushrooms from 46.31% to 72.92%. By utilizing the supply of oyster mushrooms from local farmers, the company can meet its demand and reduce the supply of oyster mushrooms from local farmers by 1.36%.